Integration of AI&ML with high speed compression Ignition engines being used on Diesel Locomotives of Indian Railways. - VERMA, narendra (PREPARE@u® | IEI Conferences, 2021)
Abstract: India has proved itself to be the major economy having the fastest growth the world over. By 2025, India’s target is to the tune of 5 trillion economy. The target is still more challenging due to the Pandemic COVID19 period. Currently, India’s GDP is about 2.78 trillion. India’s nominal GDP, estimated at about 2.74 trillion in FY20 has presently shrunk to 2.66 trillion in FY21. In particular, the focus on “Make in India” are directly influenced by the strength of India’s infrastructure. The way India has handled the COVID19 vaccination project indigenously for its 1.3 billion people is commendable and this is in line with the initiative of the Government for “Atmanirbhar Bharat”. The services sector has adversely suffered during Covid-19 pandemic. But the software services sector, an unexpected beneficiary, gained from the pandemic situation is the surging global demand for digital services, reviving client additions, top line growth and most important, hiring. India has certain SDGs mapped by NITI (National Institution for Transforming India) Aayog based on various defined indicators responding to national needs. The Government is committed to ensuring “Sabka Saath, Sabka Vikas, Sabka Vishwas” in the spirit of the Sustainable Development Goals’ motto of “Leaving No One Behind” Indian Railways is one of the largest networks for train operation and it is the fourth largest in the world. Since Railways are mainly concerned with train operation carrying passengers as well as freight services. As on 1st April 2021, the national rail network consists of 123,542 track km over a defined route of 64689 km with 7,325 stations. For efficient train operation, Railways have to maintain a large fleet of rolling stocks hence importance of locomotive cannot be ignored. These mainline diesel electric locomotives have definitely an impact on overall performance of the train operation. In view of above, the efforts are made to integrate the functioning of high-speed compression ignition engines installed on high horse power locomotives working over Indian railways. This integration has been made possible with the help of Artificial Intelligence (AI) & Machine learning (ML) the latest technological approach. By using this technology, the railways are also capable to maintain punctuality of trains & reduce failures of locomotive to the extent possible. Internal combustion engines have powered our civilization since the second industrial revolution. Today, Internal combustion engines stand at a critical intersection, seeking immediate breakthrough technologies to produce high-power and achieving near-zero carbon emissions targets. Artificial intelligence (AI), particularly with the advances in machine learning (ML) and deep learning, out-performs humans in solving many highly complex real-world problems. In recent years, AI has revolutionized a huge number of disciplines. Internal combustion engine is a complicated system that involves combustion, heat transfer, fluid dynamics, system control, and design, among other mechanisms, and thus provides a perfect yet challenging platform for AI applications. Testing and simulations of engine operations generate a huge amount of data that can be utilized to train AI models. Meanwhile, applications of AI models in model development, engine design/optimization, and control are still in their growing up stage. Interdisciplinary research on AI for internal combustion engines is needed to close this gap. Here the emphasis is laid on the introduction of Microprocessor based Locomotive Control System along with the MCBG /Microcontroller based governor which not only reduces /avoids engine failure but increases the operational efficiency of the locomotives in actual service.